Practica Socio-Comunitaria Como Herramienta Para La Articulación Con El Nivel Básico - Rosa, María José; Santa, Valeria; Mónaco, Noemí; Autrán, Valeria; Amín, María Silvana; Tamiozzo, Laura (European Scientific Journal, ESJ, 2017)
The National University of Río Cuarto, Córdoba, Argentina, called for the incorporation of Socio-Community Practices (PSC) as part of the curriculum in Higher Education. Within the framework of this innovation, the "Socio-Community Practice as a tool for articulation with the initial level at the Jorge Newbery School" was developed within the Agronomic Engineering career. This practice of socio-educational application promotes and makes possible the establishment of social networks and of more inclusive and integrating communities as pedagogical instances of university formation in contexts of solidarity. The objectives were to develop in university students socio-critical attitudes of solidarity, in an interdisciplinary framework with social actors not belonging to their academic environment and at the same time promote in children of the primary school level an ecological conscience, the consumption of healthy foods and organic products from the self-production of vegetables. In different meetings with the children of the Jorge Newbery School, the students of the Agronomic Engineering career developed thematic axes coordinated by a team of interdisciplinary teachers and professionals from the National Institute of Agricultural Technology. This experience generated networks of exchange and enriching instances of the teaching-learning process between students and teachers of differents levels.